2023
DOI: 10.3390/plants12203612
|View full text |Cite
|
Sign up to set email alerts
|

Albocycline Is the Main Bioactive Antifungal Compound Produced by Streptomyces sp. OR6 against Verticillium dahliae

Carla Calvo-Peña,
Rebeca Cobos,
José María Sánchez-López
et al.

Abstract: Verticillium wilt is a soil-borne fungal disease that affects olive trees (Olea europaea) and poses a serious threat to their cultivation. The causal agent of this disease is Verticillium dahliae, a pathogen that is difficult to control with conventional methods. Therefore, there is a need to explore alternative strategies for the management of Verticillium wilt. In this study, we aimed to isolate and characterize actinobacteria from the rhizosphere of olive trees that could act as potential biocontrol agents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…strains in suppressing the viability of V. dahliae MS could be caused by the bioactive antifungal compounds produced by these strains, such as albocycline. Thus, our hypothesis is supported by the recent study conducted by Calvo-Peña et al [36], who recently described the ability of albocycline to suppress the germination of V. dahliae conidia. However, more research in needed in order to determine the potential antifungal bioactive compounds produced by our Streptomyces spp.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…strains in suppressing the viability of V. dahliae MS could be caused by the bioactive antifungal compounds produced by these strains, such as albocycline. Thus, our hypothesis is supported by the recent study conducted by Calvo-Peña et al [36], who recently described the ability of albocycline to suppress the germination of V. dahliae conidia. However, more research in needed in order to determine the potential antifungal bioactive compounds produced by our Streptomyces spp.…”
Section: Discussionsupporting
confidence: 86%
“…Xue et al [35] observed that Streptomyces hyphae coiled around the hyphae of V. dahliae and demonstrated that the strains S. cyaneofuscatus ZY-153, S. kanamyceticu B-49, S. rochei X-4, and S. flavotricini Z-13 significantly reduced disease severity in cotton plants under both greenhouse and field conditions compared to the untreated controls. More recently, Calvo-Peña et al [36] identified albocycline, a macrolide polyketide with antibacterial and antifungal activity, as a bioactive compound produced by Streptomyces sp. OR6 that was able to suppress the germination of V. dahliae conidia.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of V. dahliae is particularly worrisome due to the pathogen's ability to persist in the soil for extended periods, which presents challenges in managing and controlling the disease. This persistence not only poses a threat to current cotton crops but also carries long‐term economic consequences for cotton production (Calvo‐Peña et al, 2023; Katan, 2000). The study of disease resistance in cotton against V. dahliae greatly benefits from the application of proteomics techniques (W. Gao et al, 2013; Li et al, 2023).…”
Section: Discussionmentioning
confidence: 99%